A biomechanically-guided planning and execution paradigm for osteoporotic hip augmentation: Experimental evaluation of the biomechanics and temperature-rise. (July 2021) - Farvardin, Amirhossein; Bakhtiarinejad, Mahsan; Murphy, Ryan J.; Basafa, Ehsan; Khanuja, Harpal; Oni, Juluis K.; Armand, Mehran
Abstract: Background: Augmentation of the proximal femur with bone cement (femoroplasty) has been identified as a potential preventive approach to reduce the risk of fracture. Femoroplasty, however, is associated with a risk of thermal damage as well as the leakage of bone cement or blockage of blood supply when large volumes of cement are introduced inside the bone. Methods: Six pairs of cadaveric femora were augmented using a newly proposed planning paradigm and an in-house navigation system to control the location and volume of the injected cement. To evaluate the risk of thermal damage, we recorded the peak temperature of bone at three regions of interest as well as the exposure time for temperature rise of 8 °C, 10 °C, and 12 °C in these regions. Augmentation was followed by mechanical testing to failure resembling a sideway fall on the greater trochanter. Findings: Results of the fracture tests correlated with those of simulations for the yield load (R 2 = 0.77) and showed that femoroplasty can significantly improve the yield load (42%, P < 0.001) and yield energy (139%, P = 0.062) of the specimens. Meanwhile, temperature recordings of the bone surface showed that the areas close to the greater trochanter will be exposed to more critical temperature rise than the trochanteric crest and femoral neck areas. Interpretation: The new planning paradigm offers a more efficient injection strategy with injection volume of 9.1 ml on average. Meanwhile, temperature recordings of bone surfaces suggest that risk of thermal necrosis remains as a concern with femoroplasty using Polymethylmethacrylate. Highlights: Osteoporotic hip augmentation improves the biomechanical properties. Finite element analysis can predict the yield fracture load of the proximal femur. Femoroplasty with Polymethylmethacrylate can cause thermal damage to the tissue.